A Decade-Long Trend in The Development of Systems Thinking Skills on Science Learning : Contributions to Elementary Schools - Yulianto, Ade; Sopandi, Wahyu; Riandi, Riandi; Hamdu, Ghullam (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to identify trends in systems thinking research within the context of science education over the past decade and providing education researchers with a global perspective on the development of systems thinking. The bibliometric analysis research method is a quantitative approach used to analyze scientific literature to identify trends, publication patterns, collaborations between authors or institutions, and emerging research topics in a field of science. Â The data used for bibliometric analysis is the research trend of systems thinking in science learning from 2014 to 2024, based on the Scopus database, utilizing the R Package Bibliometric and VosViewer Software. The obtained articles were then processed using thematic analysis techniques with the R Bibliometric Package to analyze primary information, annual scientific publications, article citations per year, total citations of top journals, Sankey diagrams, top author production, countries with the highest productivity, most productive affiliations, and thematic maps. The findings of this study indicate that research on systems thinking in science learning has experienced an annual growth rate of 9.6% and an average citation rate of 13.6 citations per document. Furthermore, it analyzes the thematic mapping of the obtained keywords, where the motor themes in this study such as curriculum, teaching, elementary school, student learning, and system theory are well-developed and essential for shaping research in systems thinking in science learning. The thematic mapping reveals a strong interconnection among three key themes: systems thinking, science learning, and elementary schools. These themes hold significant potential and are highly relevant for further exploration due to their high centrality, yet they remain relatively underexplored to date. The study of systems thinking skills in science learning should also consider previous research findings related to sustainable development goals, climate change, gender similarity, and conceptual frameworks.